BEBERAPA CATATAN TENTANG PENGEMBANGAN KELEMBAGAAN KAWASAN LINDUNG PADA ERA OTONOMI DAERAH - Tri Widodo W. Utomo (Jurnal Borneo Administrator, 2005)
The global issue on environmental degradation is becoming solemn concern among national and local governments. One of strategies in overcoming environmental problems, particularly in the shielding / caring areas (kawasan lindung), is to promote special institution in charge of composing plan, implementing programs, controlling and evaluating performance, as well as building strategic alliances among stakeholders to protect and improve the quality of shielding areas. This paper tries to analyze the probability of making new institutions based on “collaborative management” principles. In brief, it offers two models of such institution, namely, upstream – downstream solidarity; and central – regional solidarity.